Influence of Repeated Cycles of Rhythmic Extreme Whole-Body Cooling (–120°С) on Myocardium Structure in Dynamics of Rats’ Aging - Martynova, Yuliya V.; Babiichuk, Vladislav G. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(2):159.